Effectiveness of nutrition and dietary interventions for people with serious mental illness: systematic review and meta‐analysis. (2nd October 2022) - Rocks, Tetyana; Teasdale, Scott B; Fehily, Caitlin; Young, Claire; Howland, Gina; Kelly, Blair; Dawson, Samantha; Jacka, Felice; Dunbar, James A; O'Neil, Adrienne
Abstract: Objective: To review recent published trials of nutrition and dietary interventions for people with serious mental illness; to assess their effectiveness in improving metabolic syndrome risk factors. Study design: Systematic review and meta‐analysis of randomised and non‐randomised controlled trials of interventions with a nutrition/diet‐related component delivered to people with serious mental illness, published 1 January 2010 – 6 September 2021. Primary outcomes were weight, body mass index (BMI), and waist circumference. Secondary outcomes were total serum cholesterol, low‐density lipoprotein (LDL) and high‐density lipoprotein (HDL) cholesterol, triglyceride, and blood glucose levels. Data sources: MEDLINE, EMBASE, PsycINFO, CINAHL, and CENTRAL databases. In addition, reference lists of relevant publications were examined for further additional studies. Data synthesis: Twenty‐five studies encompassing 26 intervention arms were included in our analysis. Eight studies were at low or some risk of bias, seventeen were deemed to be at high risk. Eight of seventeen intervention arms found statistically significant intervention effects on weight, ten of 24 on BMI, and seven of seventeen on waist circumference. The pooled effects of nutrition interventions on metabolic syndrome risk factors were statistically non‐significant. However, we identified small size effects on weight for interventions delivered by dietitians (five studies; 262 intervention, 258 control participants; standardised mean difference [SMD], –0.28; 95% CI, –0.51 to –0.04) and interventions consisting of individual sessions only (three studies; 141 intervention, 134 control participants; SMD, –0.30; 95% CI, –0.54 to –0.06). Conclusions: We found only limited evidence for nutrition interventions improving metabolic syndrome risk factors in people with serious mental illness. However, they may be more effective when delivered on an individual basis or by dietitians. PROSPERO registration: CRD42021235979 (prospective).